Mediating effects of smoking and chronic obstructive pulmonary disease on the relation between the CHRNA5‐A3 genetic locus and lung cancer risk - Jian Wang; Margaret R. Spitz; Christopher I. Amos; Anna V. Wilkinson; Xifeng Wu; Sanjay Shete (2010)
Recent genome-wide association studies of lung cancer have shown that the CHRNA5-A3 region on chromosome 15q24-25.1 is strongly associated with an increased risk of lung cancer and nicotine dependence, and is thought to be associated with chronic obstructive pulmonary disease as well. However, it has not been established whether the association between genetic variants and lung cancer risk is a direct one or one mediated by nicotine dependence.The authors applied a rigorous statistical approach, mediation analysis, to examine the mediating effect of smoking behavior and self-reported, physician-diagnosed emphysema (chronic obstructive pulmonary disease [COPD]) on the relation between the CHRNA5-A3 region genetic variant rs1051730 and the risk of lung cancer.Our results showed that rs1051730 is directly associated with lung cancer risk, but it is also associated with lung cancer risk through its effect on both smoking behavior and COPD. Furthermore, we showed that COPD is a mediating phenotype that explains part of the effect of smoking behavior on lung cancer. Our results also suggested that smoking behavior is a mediator of the relation between rs1051730 and COPD risk.Smoking behavior and COPD are mediators of the association between the single nucleotide polymorphism (SNP) rs1051730 and the risk of lung cancer. Also, COPD is a mediator of the association between smoking behavior and lung cancer. Finally, smoking behavior also has mediating effects on the association between the SNP and COPD.